Resnica v avtobiografiji: Sporočanje resničnega v nekaterih svetovnih avtobiografijah in v Cankarjevem Mojem življenju - Avsenik Nabergoj, Irena (Slavia Centralis, 2020)
Truth in Autobiography. Representation of Reality in some Historic Autobiographies and in Ivan Cankar’s Moje življenje (’My Life’) This article discusses aspects of conveying truth in autobiography with respect to a variety of historic autobiographical works in comparison to Ivan Cankar’s autobiography, Moje življenje (’My Life’). A discussion of different viewpoints on truth and reality provides criteria for judging the authenticity and credibility of literary presentations of life experience and life stories. In this way, it is possible to see more clearly what is common and what is different in autobiographical writing compared to poetry and fiction. The aim of the article is to assess the possibilities and limits of conveying truth about life by means of confessional forms characteristic of genres of autobiography.